Konstruksi Metodologis Riba dalam Tafsir al-Jashash: Limitasi dan Kontekstualisasi terhadap Fenomena Bunga Bank Modern - Fadel Latuapo; Saifuddin Zuhri (UIN AM. Sangadji Ambon, 2026)
This study addresses the ongoing debate among religious scholars, Islamic studies academics, and economists regarding the permissibility of interest in banking credit mechanisms. Initially, it examines al-Jashash's interpretive framework in formulating rulings on riba within the classical exegetical tradition. Furthermore, this study elaborates contextual perspectives to extend beyond purely normative analysis, aiming to formulate a more comprehensive understanding and bridge the gap between classical concepts of riba and contemporary monetary systems. This study employs library research methods applying a mawḍuʿi (thematic) interpretation approach, as all data sources are bibliographic and analyzed thematically. The findings illustrate that al-Jashash's interpretive construction operates within a textual-normative framework focusing on lexical and syntactic structures, utilizing supplementary sources including the Sunnah, companions' opinions, ijma, and the socio-cultural context of Arabian society. Additionally, this study applies Abdullah Saeed's theory to examine the contextual reality of bank interest, concluding that bank interest cannot categorically be equated with riba.